Effect of Paddy Straw plus Non-Forage Fibre Sources Based Complete Rations with Different Levels of Neutral Detergent Fibre on Rumen Fermentation Parameters in Lactating Cows - Chacko, K. Biju; Mohan, K.M. Syam; Ally, K.; Shyama, K.; Anil, K. S.; Sathian, C. T. (Indian Journal of Animal Nutrition, 2017)
Eighteen dairy cows yielding approximately 10 kg of milk/d were divided into 3 groups of six each and allotted to the three experimental rations containing 25, 30 and 35% NDF in groups T1, T2 and T3, respectively to study rumen fermentation parameters and occurrence of sub-acute ruminal acidosis (SARA).Paddy straw was the sole source of roughage NDF with the rest of NDF being met from non-forage sources. The pH of rumen liquor was similar among the treatments. The TVFA content was highest (P